AB0010 Evaluation of sensitivity to dna damaging agents and efficiency of dna repair in human peripheral blood mononuclear cellsfrom patients with dermatomyositis and polymyositis. (12th June 2018) - Brzezinska, O.; Macieja, A.; Lewandowska-Polak, A.; Sarnik, J.; Kubicka, M.; Makowska, J.; Popławski, T.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) being one of the connective tissue diseases are a group of diseases with not fully understood pathology. The common features are production of autoantibodies, abnormal immune response against self-antigens and inflammatory process leading to destruction of muscle cells and internal organ involvement. Patients with inflammatory myopathies have higher risk of developing cancers. One of the processes that can attribute to increased risk of cancers can be genomic instability and impaired DNA repair. Objectives: The aim of the study was to assess the processes of endogenous and exogenous DNA damage and its repair in patients with IIM as compared to healthy controls. Methods: The study included 10 patients (9 men and 1 woman, mean age 46, 6±16, 5) with idiopathic inflammatory myopathies (dermatomyositis or polymyositis) as well as 7 healthy control individuals (4 men and 3 women, mean age 33, 8±9, 8). DNA damage and repair were investigated by the comet assay. To perform the comet assay human peripheral blood mononuclear cells (PBMCs) were isolated and incubated with tert-butyl hydroperoxide (t-BOOH) or bleomycin. Both compounds are common DNA damaging agents – t-BOOH induces oxidative DNA lesions whereas bleomycin induces also DNA double strand breaks (DSBs). To test the DNA repair capability, PBMCs were allowed to recover for 2 hour. The level of endogenous DNA lesions was also investigated. Results: The levels of endogenous DNA damage were not statistically significantly different between tested groups (IIM-3, 3±3, 6% vs 3, 2±3, 8% in control; p=0, 648). The extent of the DNA damage induced by bleomycin (IIM-23, 3±19, 5% vs 9, 8±5, 9% in control) as well as oxidative stress (IIM-14, 7±16, 2% vs 10, 4±7, 4% in control) was significantly higher in PBMS derived from IIM patients than in healthy counterparts (p<0, 001). Kinetic curves of DNA repair are different but the background mechanism underlying observed differences in the repair curve between healthy subjects and patients need to be evaluated further. Conclusions: Understanding the etiology of this phenomena in these diseases may provide insight into disease pathogenesis and explain the increased susceptibility of patients to malignancies. Finding the patients with increased DNA instability could potentially serve as a biomarker and indicate the group of patients who should be carefully screened for neoplasmatic disorder. Disclosure of Interest: None declared